Structured type 1 diabetes education delivered in routine care in Australia reduces diabetes-related emergencies and severe diabetes-related distress: The OzDAFNE program. (February 2016) - Speight, Jane; Holmes-Truscott, Elizabeth; Harvey, Dianne M.; Hendrieckx, Christel; Hagger, Virginia L.; Harris, Susan E.; Knight, Brigid A.; McIntyre, Harold D.
Highlights: A real-world evaluation of a structured type 1 diabetes education program. At follow up, diabetes-related distress and emergencies significantly reduced. Clinically significant reduction in HbA1c among those with highest baseline levels. Structured education within routine practice offers clinically important benefits. Abstract: Aims: To evaluate structured type 1 diabetes education delivered in routine practice throughout Australia. Methods: Participants attended a five-day training program in insulin dose adjustment and carbohydrate counting between April 2007 and February 2012. Using an uncontrolled before-and-after study design, we investigated: HbA1c (% and mmol/mol); severe hypoglycaemia; diabetes ketoacidosis (DKA) requiring hospitalisation, and diabetes-related distress (Problem Areas in Diabetes scale; PAID), weight (kg); body mass index. Data were collected pre-training and 6–18 months post-training. Change in outcome scores were examined overall as well as between groups stratified by baseline HbA1c quartiles. Data are mean ± SD or % ( n ). Results: 506 participants had data eligible for analysis. From baseline to follow-up, significant reductions were observed in the proportion of participants reporting at least one severe hypoglycaemic event (24.7% ( n  = 123) vs 12.1% ( n  = 59), p  < 0.001); and severe diabetes-related distress (29.3% ( n  = 145) vs 12.6% ( n  = 60), p  < 0.001). DKA requiring hospitalisation in the past year reduced from 4.1% ( n  = 20) to 1.2% ( n  = 6). For those with above target baseline HbA1c there was a small, statistically significant improvement ( n  = 418, 8.4 ± 1.1% (69 ± 12 mmol/mol) to 8.2 ± 1.1% (66 ± 12 mmol/mol). HbA1c improvement was clinically significant among those in the highest baseline quartile ( n  = 122, 9.7 ± 1.1% (82 ± 11 mmol/mol) to 9.0 ± 1.2% (75 ± 13 mmol/mol), p  < 0.001). Conclusions: The proportion of participants reporting severe hypoglycaemia, DKA and severe diabetes-related distress was at least halved, and HbA1c reduced by 0.7% (7 mmol/mol) among those with highest baseline levels. Structured type 1 diabetes education delivered in routine practice offers clinically important benefits for those with greatest clinical need.